A genetically determined molecular switch modulates the anti-inflammatory potential of human IgA - Gibson, Andrew W.; Wu, Jianming; Hendrickson, R. Curtis; Ptacek, Travis; Mobley, James; Edberg, Jeffrey C.; Kimberly, Robert P. (Frontiers in Immunology, 2025)
Fc receptor-driven immune system activity typically reflects a balance of activating and inhibitory mechanisms, mediated by the immunoreceptor tyrosine-based activation motif (ITAM) or inhibition motif (ITIM) in the ligand-binding alpha chain (FcγRIIa – c) or the canonical ITAM in the associated Fc receptor γ-chain (FcRγ). A second role for the ITAM, an inhibitory role known as ITAMi, was initially recognized for the FcαRI-FcRγ signaling pair. We report an FcRγ-independent mechanism for inhibitory signaling by the IgA-binding receptor, FcαRI (CD89) in which the natural Ser248Gly variant in the cytoplasmic domain of the FcαRI α-chain alters the signaling capacity of FcαRI and constitutes a serine-based genetically determined switch for regulation of the anti- and proinflammatory potentials of human IgA. To elucidate the basis for this α-chain mechanism, we sought allele-specific FcαRI-associated molecules. Sab (SH3BP5), a trans-inhibitor for Bruton’s tyrosine kinase (Btk), is recruited by the more common Ser248 allele, whereas the src-family tyrosine kinase Lyn, a Btk activator, is reciprocally recruited by the Gly248 variant. Ser248 phosphorylation amplifies Sab association and disrupts Lyn binding through an overlapping region containing an unconventional SH3-domain binding motif. In contrast to FcαRI Gly248, recruitment of Sab by FcαRI Ser248 results in inhibition of Btk activation and suppression of IgA effector functions independent of FcRγ-pairing. Expression of a dominant-negative Sab construct releases FcαRI-mediated inhibition in a Ser248- allele-specific manner. These findings reveal a reversible serine-based phosphorylation-dependent molecular switch for regulation of receptor-mediated activation/inhibition that couples FcαRI α-chain to divergent inflammatory properties of human IgA.